Nonlinear Robust Controller Applied to an Antilock Braking System With Estimation of Parametric Uncertainties and External Perturbations - Cuauhtemoc Acosta Lua; Stefano Di Gennaro (IEEE Access)
The Anti–lock Braking System (ABS) is an active safety feature that reduces braking distance in automobiles by preventing the wheels from locking and skidding. Achieving optimal braking conditions is challenging due to the nonlinear dynamics and parametric uncertainties present in both the longitudinal dynamics of the vehicle and the wheel dynamics. To address this issue, this paper proposes a nonlinear robust controller that, using an estimator designed with High Order Sliding Mode (HOSM), estimates the parametric uncertainties and external perturbations and ensures the tracking of the desired references. The proposed controller’s performance has been validated through numerical simulations using CarSim and real–time experiments on an ABS laboratory setup, representing a quarter–car model. Quantitative results demonstrate the controller’s effectiveness, achieving reductions in key performance indicators (KPIs), such as the Mean Squared Error (MSE) of the slip tracking error and the Mean Absolute Error (MAE), compared to a baseline controller without the HOSM estimator. Additionally, the controller ensures finite–time estimation of uncertain parameters and external disturbances, enabling faster and more efficient braking. These results highlight the practical potential of the proposed methodology in enhancing automotive braking systems.